Influence of Nitrogen Ion Implantation on Deformation and Fatigue Properties of TiNi Shape-Memory Alloy Wire (Archives of Mechanics - Test, 2013)
A shape memory alloy (SMA) is expected to be applied as intelligent material since it shows the unique characteristics of the shape memory effect and superelasticity. Most SMA elements, with these characteristics, perform cyclic motions. In these cases, fatigue of SMA is one of the important properties in view of evaluating functional characteristics. The fatigue properties are complex since they depend on stress, strain, temperature and time. If SMA is implanted by high energy ions, the thermomechanical properties may change, resulting in long fatigue life. In the present study, the nitrogen ion implantation was applied to modify TiNi SMA wire surface and the influence of implantation treatment on the tensile deformation and bending fatigue properties was investigated.